Public health management strategies to combat and mitigate social stigma in the MPOX outbreak - Norberg, Antonio Neres; Norberg, Paulo Roberto Blanco Moreira; Manhães , Fernanda Castro; Filho, Renato Mataveli Ferreira; Souza, Davydson Gerhardt de; Queiroz, Margareth Maria de Carvalho; Neto, Carlos Henrique Garção; Boechat, Júlio Cesar dos Santos; Viana, Kelen Salaroli; Silva, Marly Torres Rodrigues da (Seven Editora, 2024)
In May 2022, an outbreak of the Mpox virus was observed in several countries, precipitating a rapid spread worldwide. The current Mpox outbreak has unusual characteristics compared to previous outbreaks. A salient peculiarity is the remarkable incidence of confirmed cases among men who have sex with men. The aim of this research is to discern, within the current scientific literature, the most pertinent and effective public health strategies to prevent or mitigate Mpox-related social stigmatization. Using the PRISMA model, a systematic review was conducted using the PubMed, SciELO, and Google Scholar databases, covering articles published from January 2022 to January 2024. Public health strategies to prevent or mitigate social stigmatization of Mpox were systematically recorded and summarized for subsequent analysis. Seven articles were identified and analyzed. None of the articles evaluated presented a comprehensive approach to public health strategies to combat social stigmatization in the midst of the Mpox outbreak. The studies examined emphasize the central role of interventions in three axes of public health strategies: awareness and training of health professionals, targeted communication that is sensitive to the needs of the different affected groups, and medical care measures that guarantee anonymity and respect for patients. Confronting the proposed strategies with the key issues that trigger stigmatisation, it becomes clear that a differentiated calibration of these strategies is needed to optimise the effectiveness of the implementation of public health guidelines. In addition, attention to the mental health of patients with Mpox is a crucial dimension that cannot be neglected, given the psychological vulnerability of these individuals, resulting from both the disease itself and social stigmatization. DOI:https://doi.org/10.56238/sevened2024.001-029